Determination of Digital Marketing Strategies As Effective Communication Techniques For GoOntravel Brand Awareness - Samran, Zaqrona; Wahyuni, Sri; Misril, Misril; Nabila, Rana; Putri, Anne (Journal of Research in Marketing (ISSN: 2292-9355), 2018)
The rapid development of ITC (Information Communication Technologies), digital marketing is very relevant to be applied in communicating its products effectively to the target communities. GoOntravel is an integrated tourism retail market that empowers people as the main actors in providing tourism services that will meet all the needs of customers or tourists. This study used qualitative research methods. Data collection is done by observation, documentation, and interviews. The results show digital marketing strategies that GoOntravel can do to increase brand awareness.